Study of antihyperglycaemic activity in streptozotocin induced diabetic mice and antioxidant activities of medicinal plant extracts - Thu, Nguyen Thi Xuan; Long, Dang Duc; Thuy, Thanh Thi Thu (Academia Journal of Biology, 2019)
Some extracts of medicinal plants have demonstrated potential benefits in treatment of different diseases for centuries such as antihyperglycemic, antioxidant, anti-inflammatory, antibacterial. The purpose of this study is to evaluate the effect of extracts from several herbal plants, such as Gymnema sylvestre, Stevia rebaudiana, Cinnamomum cassia, Zea may, Ocimum basilicumon blood glucose level in streptozotocin (STZ) induced diabetic miceand to offer scientific proofs for the identified antihyperglycemic effect by investigating on mechanismsof the most effective extract. The results proved that diabetic mice treated with 70% ethanol extracts of Gymnema sylvestre leaves and Stevia rebaudiana leaves showed significant reduction of the blood glucose levels at a dose of 500 mg/kg body weight when compared to control (p<0,05). Antihyperglycemic activity of Gymnema sylvestre (57,68%) and Stevia rebaudiana extracts (54,93%) were significantly higher than other extracts. The inhibition of α-amylase and α-glucosidase activity of Gymnema sylvestreand, Stevia rebaudiana extracts were carried out in vitro. The result demonstrated that these Gymnema sylvestre and Stevia rebaudiana extracts exerted significant inhibition and specific on intestinal α-amylase and α-glucosidases activities. Using 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay showed that Gymnema sylvestre and Stevia rebaudiana extracts exhibited relatively low antioxidant activity with the concentration of a sample required for 50% scavenging of the DPPH free radical of 115,88 ± 1,16 µg/ml and 160,27 ± 2,01 µg/mlcompared to vitamin C (49,16 ± 1,26 µg/ml).